Forum: Attempting a dialectical reconciliation of the concept truth in the objectivism of evangelical Christianity and the relativism of postmodernism - E. K. Foshaugen (Acta Theologica)
The Church faces a number of challenges concerning the sociological impact postmodernism is having on society. One significant area that has been profoundly disputed is the epistemological content of the concept of truth. Evangelical Christians believe in Objectivism: the conviction that there exists some ahistorical source, foundation or framework to which we can appeal to in  determining the substance and nature of truth, knowledge, reality, right or wrong — and it is independent and external to personal experience or thinking. However, many no longer believe in absolute truth but in relativism. Relativism is the denial that there exists such an ahistorical source or foundation that we can appeal to. Truth, knowledge, reality, right and wrong are all concepts that are relative to a specific conceptual scheme, framework, or paradigm founded in a society, religion and culture. This article represents an endeavour to dialogically reunite the two perspectives by arguing for the seeking of the “truths” in both perspectives. God is Objective Truth and has become involved in history: in the existential; in the material setting of our relative and infallible thoughts and the slanted interpretative experiences of the Triune God and life. The synthesis will be an affirmation that for Christians Truth is discovered and revealed in fellowship within community. And members of the Body of Christ are first and finally called to reveal and demonstrate truth to the world — in their unity.